Auriculopuntura modifica la secreción salival en sujeto sano - Ruiz Hernández, Mayra Verónica (Universidad Autónoma Metropolitana, 2018)
Introduction Different points of the auricle are used in the treatment of alterations of the salivary secretion; however, its mechanism of action and effect on the activity of the autonomic nervous system (ANS) have not been described. The variability of the heart rate (HRV) and especially its frequency domain parameters are used to know the equilibrium state of the sympathetic and parasympathetic function of the ANS. It has been described that the effect of acupuncture on the physiology and pathophysiology of ANS may depend on the basal state of the subjects. Objective Examine the changes of non stimulated salivary secretion (NSSS) and correlate it with the parameters of the time and frequency domain of HRV in healthy subjects before and after the application of acupuncture in the points Salivary gland 2 and solar plexus of the auricle; comparing the effect of this intervention on a global sample versus two groups: (A) with a lower rate of salivary secretion and (B) with a higher rate of salivary secretion. Materials and methods Auriculopuncture was applied in GS2 and SP in 26 healthy subjects of either sex. Before (and immediately after) the auriculopuncture the (NSSS) was measured and 5-minute electrocardiographic recordings were made; and the time domain and frequency parameters of the HRV were obtained. The pre and post auriculopuncture values were compared between the total sample and two groups of this: A with lower rate of salivary secretion and B with higher rate of salivary secretion. Results In basal conditions the (NSSS) correlated positively and significantly with the RMSSD in the total group; in group A and B with PNN50 and RMSSD in a positive and significant way in both cases. After the application of auriculopuncture in GS2 and SP salivary secretion decreased non-significantly in the total group; increased significantly in group A; and decreased non-significantly in group B. Regarding the frequency domain measurements of HRV: the treatment facilitated the following changes: decrease in HF; increase in LF and LF/HF, in all cases these changes were not significant in the total group; HF decreased, LF and LF/HF increased, in all cases changes were not significant in group A; HF decreased, LF and LF / HF increased, in all cases changes were not significant in group B. Pearson correlation coefficient examinations showed the following correlations between the consecutive changes to the salivary secretion auriculopuncture treatment and the frequency parameters of the heart rate variability: in group A, a negative correlation with HF with a tendency to be significant, and positive with LF and LF/HF, in the first case with a tendency to be significant and in the second case not significant in the total group; in group B a negative correlation with HF; and positive with LF and LF/HF, in all cases significant; a negative correlation with HF; positive with LF and negative with LF/HF, in all cases not significant. Regarding Pearson correlations between changes in frequency domain measurements due to auriculopuncture treatment, it was observed that HF versus LF and HF versus LF/HF had an inversely proportional correlation and LF versus LF/HF a directly proportional correlation, in all cases these correlations were significant. Conclusions The (NSSS) in baseline conditions showed a direct correlation with the measurement of the RMSSD time parameter of the HRV, which in turn correlates with the level of parasympathetic activity. While the changes observed in the (NSSS) and the frequency domain parameters of the HRV after the auriculopuncture in the points GS2 and PS are compatible with a change towards the sympathetic predominance in the parasympathetic-sympathetic balance of the ANS evaluated by means of the HRV. Key words: salivary secretion, heart rate variability, Salivary Gland 2, Solar Plexus, autonomic nervous system.; Diversos puntos del pabellón auricular se emplean en el tratamiento de alteraciones de la secreción salival; sin embargo, su mecanismo de acción y su efecto sobre la actividad del sistema nervioso autónomo (SNA) no han sido descritos. La variabilidad de la frecuencia cardiaca (VFC) y en especial sus parámetros del dominio de frecuencia se emplean para conocer el estado de equilibrio de la función simpática y parasimpática del SNA. Se ha descrito que el efecto de la acupuntura sobre la fisiología y fisiopatología del SNA puede depender del estado basal de los sujetos. Objetivo Examinar los cambios de la secreción salival no estimulada (SSNE) y correlacionarla con los parámetros del dominio de tiempo y frecuencia de la VFC en sujetos sanos antes y después de la aplicación de acupuntura en los puntos Glándula Salival 2 y Plexo Solar del pabellón auricular; comparando el efecto de esta intervención en una muestra global versus dos grupos: (A) con tasa de secreción salival menor y (B) con tasa de secreción salival mayor. Materiales y métodos Se aplicó auriculopuntura en GS2 y PS en 26 sujetos sanos de cualquier sexo. Antes e inmediatamente después de la auriculopuntura se midió la (SSNE) y se realizaron registros electrocardiográficos de 5 min; y se obtuvieron los parámetros de dominio de tiempo y frecuencia de la VFC. Se compararon los valores pre y pos auriculopuntura entre la muestra total y dos grupos de esta: A con tasa de secreción salival menor y B con tasa de secreción salival mayor. Resultados En condiciones basales la (SSNE) se correlacionó de manera positiva y significativa con el RMSSD en el grupo total; en el grupo A y B con el PNN50 y RMSSD de manera positiva y significativa en ambos casos. Después de la aplicación de auriculopuntura en GS2 y PS la secreción salival disminuyó de manera no significativa en el grupo total; aumentó de manera significativa en el grupo A; y disminuyó de manera no significativa en el grupo B. Respecto a las mediciones del dominio de frecuencia de la VFC: el tratamiento facilitó los siguientes cambios: disminución de HF; incremento en LF y LF/HF, en todos los casos estos cambios fueron no significativos en el grupo total; HF disminuyó, LF y LF/HF aumentaron, en todos los casos los cambios fueron no significativos en el grupo A; HF disminuyó, LF y LF/HF aumentaron, en todos los casos los cambios fueron no significativos en el grupo B. Los análisis mediante el coeficiente de correlación de Pearson mostró las siguientes correlaciones entre los cambios consecutivos al tratamiento con auriculopuntura de la secreción salival y en los parámetros de frecuencia de la variabilidad de la frecuencia cardiaca: en el grupo A, una correlación negativa con HF con una tendencia a ser significativa, y positiva con LF y LF/HF, en el primer caso con tendencia a ser significativa y en el segundo no significativa en el grupo total; en el grupo B una correlación negativa con HF; y positiva con LF y LF/HF, en todos los casos significativa; una correlación negativa con HF; positiva con LF y negativa con LF/HF, en todos los casos no significativa. Respecto a las correlaciones de Pearson entre los cambios en las mediciones del dominio de frecuencia debidos al tratamiento con auriculopuntura, se observó que HF versus LF y HF versus LF/HF tuvieron una correlación inversamente proporcional y LF versus LF/HF una correlación directamente proporcional, en todos los casos estas correlaciones fueron significativas. Conclusiones La (SSNE) en condiciones basales mostró una correlación directa con la medición del parámetro de tiempo RMSSD de la VFC, que a su vez se correlaciona con el nivel de actividad parasimpática. Mientras que los cambios observados en la (SSNE) y los parámetros de dominio de frecuencia de la VFC después de la auriculopuntura en los puntos GS2 y PS son compatibles con un cambio hacia el predominio simpático en el equilibrio parasimpático-simpático del SNA evaluado por medio de la VFC. Palabras clave: secreción salival, sistema nervioso autónomo, variación de la frecuencia cardiaca, punto Glándula Salival 2, punto Plexo Solar.